Mutual Learning Transfer Between Wrestling and Sumo as Similar Combat Sports Activities: Impact on Youth’S Technical Performance and Intrinsic Motivation - Aedo-Munoz, E (OVS LLC, 2024)
Objectives. This study aimed to compare the effects of wrestling and sumo wrestling as similar combat sports activities in a training program on technical wrestling scores, wrestling performance indexes, and intrinsic motivation in youth practitioners. Materials and methods. A randomized controlled trial using a single-blinded design, and repeated measures of parallel groups (sumo-based group: EG, n = 19, aged = 12.42 ± 0.87 years; and only wrestling group: CG, n = 19, aged = 12.41 ± 0.78 years) was conducted. Three 65-minute weekly sessions for four weeks were dedicated to the interventions. A two-factor mixed analysis of variance (ANOVA) model with repeated measures was performed to assess the group vs. time impact analysis. Results. The findings revealed a significant interaction between the variables, whereby higher values were observed for technical wrestling scores on the attempted head and arm throw test (F1;18 = 356.2; p < 0.001; ES = 0.60), wrestling performance indexes on the pushing opponent test (F1;18 = 8.31; p = 0.009; ES = 0.08), intrinsic motivation for effort/ importance item (F1;18 = 12.24; p = 0.003; ES = 0.82) and intrinsic motivation item (F1;18 = 19.36; p = 0.000; ES = 0.24) in favor of EG. Conclusions. In conclusion, the sumo-based training program produces significantly greater responses on technical performance, and intrinsic motivation, specifically regarding wrestling training. © Melki, H., Hernandez-Martinez, J., Herrera-Valenzuela, T., Cid-Calfucura, I., Magnani Branco, B. H., & Valdés-Badilla, P., 2024.